Inclusion of Solvent Extracted Karanj (Pongamia glabra) Cake in the Diet and Production Performance of Layer Chicken - Raju, M.V.L.N.; Prakash, B.; Nagarjuna, B.V. R.; Nischala, T.; Rao, S.V. Rama; Reddy, M. R.; Panda, A. K. (Indian Journal of Animal Nutrition, 2018)
A total of 160 White Leghorn laying chicken (Lohmann) of 50 weeks of age were divided into four groups having 10 replicates of 4 chicken in each group. Solvent extracted karanj (Pongamia glabra) cake (SKC) wasincluded in the diet at graded levels (0, 6, 9 and 12%) on iso-nitrogenous and iso-caloric basis and fed to the treatment groups from 50 to 61 weeks (3 laying periods of 4 weeks each) ad lib. The egg production and eggmass decreased (P